The classroom library as a space for the interaction of readers: Discovering interpretive paths and plural readings for integral formation - Acosta Gómez, Israel (2023)
Reading expands, it is a process to establish a dialogical circle. It is an area where the multiplicity of wonders inhabits, of plural ways of reading. To do this, the classroom library allows readers to build, erect their reading; participating with their experiential certainties, their “appropriations”, from that place that implies meeting and talking, because it is from the contributions of various readers that understanding is built (Cassany, 2003). In this sense, the objective of this article is to expose a critical-creative literary reading experience, from the library itself as a relational space, to share and learn between readings, for the construction of plural assimilations, because it makes sense to share experiences and socialize. what is understood from each reading individuality. Consequently, this paper will show some practices of literary reading mediated by literary conversation as a situation of dialogic and participatory teaching, in order to demonstrate how different knowledge and ways of approaching discourse co-inhabit in the experiences of readers. literary, from where an important "axiological growth" is generated (Álvarez-Álvarez and Gutiérrez-Sebastián, 2017) that contributes to the integral formation of the readers themselves as social beings